Comprehensive transcriptome profiling of silvertip tetra (Hasemania nana), a new freshwater fish model for gender classification based on color and establishment of a caudal fin-derived cell line - Lee, Hwa Jin; Lee, Mi-Gi; Cho, Jeong-Hyeon; Kim, Min Sun; Lee, Sang Yoon (Frontiers in Marine Science, 2025)
IntroductionThis study aimed to propose the silvertip tetra (Hasemania nana) as a new experimental fish model. The silvertip tetra is a freshwater species that exhibits clear sexual dimorphism, with distinct differences in body coloration between males and females.MethodsWe analyzed the embryonic development of silvertip tetra and investigated transcriptome-level differences in gene expression between male and female brain-pituitary, caudal fin, and gonadal tissues. Additionally, we established a primary cell line derived from the caudal fin of male silvertip tetra and optimized the culture conditions for this cell line.Results and DiscussionThe optimal cell growth temperature was identified as 32°C, with a doubling time of approximately 28 hours. Successful transfection of foreign genes was confirmed by fluorescent protein expression, which was observed within 48 hours of transfection. RNA-seq analysis identified differentially expressed genes (DEGs) between sexes and tissues, particularly those involved in pigmentation, and protein interaction networks were examined to explore sex-related differences. The RNA-seq results validated by qRT-PCR suggest that the transcriptome-level gene expression patterns observed in silvertip tetra play critical roles in physiological functions and sexual dimorphism. Our findings highlight the potential of silvertip tetra as a valuable experimental model for studying pigmentation and sexual dimorphism.